Spectroelectrochemical Analysis of Oxygen Evolution by Nickel Hydroxide: Role of Oxygen Vacancies, Charge Transfer, and Silk Fibroin - Eduardo R. do Nascimento; Michele L. deSouza; Alexandre G. Brolo; Wendel A. Alves (Advanced Materials Interfaces, 2025)
Abstract This study investigates the oxygen evolution reaction (OER) on nickel hydroxide (Ni(OH)₂) catalysts, focusing on the roles of oxygen vacancies (Ov), charge transfer, and silk fibroin. Spectroelectrochemical techniques, including in situ surface‐enhanced Raman (SERS) and UV–vis spectroscopy, revealed that Ov formation and Ni‐to‐Au charge transfer facilitate the generation of high‐valence Ni and superoxide species. A Mars–van Krevelen mechanism is proposed to describe the participation of lattice oxygen. Silk fibroin is found to enhance catalytic activity by lowering the activation energy of key intermediates, as indicated by higher transfer coefficients and Tafel slope analysis. At +300 mV overpotential, fibroin‐modified samples exhibited intrinsic turnover frequencies (TOFs) of ≈0.7 s⁻¹, outperforming fibroin‐free counterparts (≈0.4 s⁻¹). These results highlight the synergy between structural defects and interfacial modifications in improving Ni(OH)₂‐based OER catalysts for sustainable energy applications.